Normative Legal Theory in the Perspective of Neo-Kantian School of Thought: Teori Hukum Normatif Dalam Perspektif Aliran Pemikiran Neo Kantian - Meidaniasari, Annisa (Lex Renaissance, 2025)
This research aims to examine the relationship between law, norms, and ethics within the societal context, as well as the role of normative legal theory from the perspective of Neo Kantian thinkers, focusing on ontological, epistemological, and axiological aspects. The importance of this study lies in understanding how normative legal theory serves not only as a positive system but also meets moral standards. The research uses a normative legal approach with historical and comparative methods, incorporating a qualitative analysis of the thoughts of several Neo Kantian thinkers, allowing for the identification of strengths and weaknesses in their perspectives. The study relies on secondary legal materials, such as legal journals, and employs literature review techniques to gather data. The findings reveal that the connection between law, norms, and ethics is essential in establishing a fair and harmonious social order. Justice should be a central principle in legal reasoning, not only based on the application of laws but also incorporating social, political, economic, and cultural elements. The exploration of normative legal theory from the Neo Kantian viewpoint provides valuable insights into the relationship between legal norms and moral principles, emphasizing the significance of rationality and individual autonomy in legal enforcement. This perspective fosters legal reforms that are more responsive to societal needs and aspirations. In conclusion, this research highlights the role of normative legal theory in the Neo Kantian tradition, which stresses rationality and individual autonomy, and advocates for legal reforms that better address contemporary societal challenges.